Side effects of X‐ray irradiation on flight ability of Cydia pomonella moth - Huang, Sheng‐Wang; Zhang, Jing‐Han; Wei, Zi‐Han; Yang, Xian‐Ming; Wang, Xing‐Ya; Yang, Xue‐Qing (Pest management science, 2024)
BACKGROUND The sterile insect technique (SIT) has proven to be an effective approach in managing the population of major invasive pests. Our previous studies showed that irradiation of Cydia pomonella males at a dosage of 366 Gy X‐rays resulted in complete sterility. However, the mating competitiveness of sterilized males is significantly compromised, which can be attributed to a decline in their ability to fly. RESULTS In this study, we examined the flight patterns of both male and female adults of C. pomonella. The results revealed significant variations in the average flight speed of both genders at different stages of maturity, with females displaying longer flight duration and covering greater distances. Effect of irradiation on the flight performance of 3‐day‐old male moths was further evaluated, as they demonstrated the longest flight distance. The findings indicated a significant decrease in flight distance, duration, and average speed, due to wing deformities caused by irradiation, which also limited the dispersal distance of moths in orchards, as indicated by the mark‐and‐recapture assay. Reverse‐transcription quantitative polymerase chain reaction analysis revealed a down‐regulation of flight‐related genes such as Flightin, myosin heavy chain, and Distal‐less following radiation exposure. CONCLUSION These findings demonstrate that X‐ray irradiation at a radiation dose of 366 Gy has a detrimental effect on the flight ability of male C. pomonella adults. These insights not only contribute to a better understanding of how radiation sterilization diminishes the mating competitiveness of male moths, but also aid in the development and improvement of SIT practices for the effective control of C. pomonella. © 2023 Society of Chemical Industry. X‐ray irradiation at a radiation dose of 366 Gy has a detrimental effect on the flight performance, including flight distance, duration, and average speed of male C. pomonella adults, probably caused by the development of wing deformities and down‐regulation of the expression of flight‐related genes.